An Interaction of Physical Self-Concept and Coach-Oriented and Self-Regulated Training Styles in Acquisition, Retention and Transfer of a Volleyball Skill in Collegiate Girls - Shila Safavi; Maryam Nezakatolhosayne; Elham Abedi (University of Tehran, 2017)
A match of the students' traits and teaching and training styles of sport skills has received researchers' attention. The aim of the present study was to investigate the interaction of physical self-concept and coach-oriented and self-regulated training styles in acquisition, retention and transfer of volleyball serve of collegiate female students. 50 female students (age: 18-25) were assigned to high and low physical self-concept groups. Then, each group was divided into coach-oriented and self-regulated styles. Participants exercised the criterion task for 6 weeks, 4 sessions per week in their special training condition. AAHPERD test and Physical Self-Concept Questionnaire were used for data collection. Acquisition tests were administered every week while retention and transfer tests were administered 3 days after the last training session and one hour after the retention test respectively. The data were analyzed by ANOVA with repeated measures and ANOVA. Results showed that the high self-concept group practicing the task with self-regulated style showed the best performance in acquisition, retention and transfer phases. The other groups showed similar performances. Results clearly showed that participants with high physical self-concept who exercised volleyball serve skill with self-regulated style had the highest skill acquisition and learning.